ChemInform Abstract: The Au(I) Catalyzed Activation of Allenamides and Their Subsequent Transformation into Chromanes: A Method for the Regiocontrolled Addition to the α‐ and γ‐Positions of the Allene Unit. Issue 10 (March 2015) - Slater, Natasha H.; Brown, Natalie J.; Elsegood, Mark R. J.; Kimber, Marc C.
Abstract The formal [3 + 3] cycloaddition of phenols with oxazolidinone derived allenamides in the presence of Au(I)‐catalysts is developed.